Physicochemical and Sensory Characteristics of Black Grass Jelly Drink on Variations in Type and Concentration of Hydrocolloids - Fitriatun Nur 'Abidah; Pepita Haryanti; Karseno Karseno (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
Sokawera Village is a village located in Cilongok District, Banyumas Regency, Central Java Province. The village has one of the most abundant agricultural commodities, namely black grass jelly. There are many black grass jelly plants and there is enough potential to be developed in the village. This study aims to determine the physicochemical and sensory characteristics of black grass jelly drink which is influenced by the type of hydrocolloid and the hydrocolloid concentration, and to determine the combination of type and concentration of hydrocolloid which produces the best physicochemical and sensory characteristics of black grass jelly drink. This study used a factorial Completely Randomized Design method with two factors, namely the type of hydrocolloid (J) which consisted of 2 levels (carrageenan and jelly powder) and the concentration of hydrocolloid (K) which consisted of 4 levels (0.4; 0.5;0,6; & 0,7%). The test variables for physicochemical characteristics include viscosity, pH, water activity (Aw), syneresis, ash content, and water content, as well as testing for sensory properties including color, aroma, taste, texture, and overall preference. The test results of physicochemical and sensory variables were analyzed using analysis of variance and DMRT at the level of = 5%. The results showed that the type of carrageenan hydrocolloid produced a jelly drink of black grass jelly with a lower viscosity and higher syneresis than the type of jelly powder hydrocolloid. Hydrocolloid concentration of 0.7% produced better physicochemical and sensory characteristics of black grass jelly drink than hydrocolloid concentration of 0.4; 0.5; and 0.6%. The best treatment in this study was obtained in the combination of 0.7carrageenan treatment (J1K4).